Genetic KCa3.1-deficiency produces locomotor hyperactivity and alterations in cerebral monoamine levels. - Kate Lykke Lambertsen; Jan Bert Gramsbergen; Mithula Sivasaravanaparan; Nicholas Ditzel; Linda Maria Sevelsted-Møller; Aida Oliván-Viguera; Maj Rabjerg; Heike Wulff; Ralf Köhler (PLoS ONE, 2012)
The calmodulin/calcium-activated K(+) channel KCa3.1 is expressed in red and white blood cells, epithelia and endothelia, and possibly central and peripheral neurons. However, our knowledge about its contribution to neurological functions and behavior is incomplete. Here, we investigated whether genetic deficiency or pharmacological activation of KCa3.1 change behavior and cerebral monoamine levels in mice.In the open field test, KCa3.1-deficiency increased horizontal activity, as KCa3.1(-/-) mice travelled longer distances (≈145% of KCa3.1(+/+)) and at higher speed (≈1.5-fold of KCa3.1(+/+)). Working memory in the Y-maze was reduced by KCa3.1-deficiency. Motor coordination on the rotarod and neuromuscular functions were unchanged. In KCa3.1(-/-) mice, HPLC analysis revealed that turn-over rates of serotonin were reduced in frontal cortex, striatum and brain stem, while noradrenalin turn-over rates were increased in the frontal cortex. Dopamine turn-over rates were unaltered. Plasma catecholamine and corticosterone levels were unaltered. Intraperitoneal injections of 10 mg/kg of the KCa3.1/KCa2-activator SKA-31 reduced rearing and turning behavior in KCa3.1(+/+) but not in KCa3.1(-/-) mice, while 30 mg/kg SKA-31 caused strong sedation in 50% of the animals of either genotypes. KCa3.1(-/-) mice were hyperactive (≈+60%) in their home cage and SKA-31-administration reduced nocturnal physical activity in KCa3.1(+/+) but not in KCa3.1(-/-) mice.KCa3.1-deficiency causes locomotor hyperactivity and altered monoamine levels in selected brain regions, suggesting a so far unknown functional link of KCa3.1 channels to behavior and monoaminergic neurotransmission in mice. The tranquilizing effects of low-dose SKA-31 raise the possibility to use KCa3.1/KCa2 channels as novel pharmacological targets for the treatment of neuropsychiatric hyperactivity disorders.